2011
DOI: 10.3390/atmos2020182
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from Ethanol-Gasoline Blends: A Single Particle Perspective

Abstract: Due to its agricultural origin and function as a fuel oxygenate, ethanol is being promoted as an alternative biomass-based fuel for use in spark ignition engines, with mandates for its use at state and regional levels. While it has been established that the addition of ethanol to a fuel reduces the particulate mass concentration in the exhaust, little attention has been paid to changes in the physicochemical properties of the emitted particles. In this work, a dynamometer-mounted GM Quad-4 spark ignition engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 67 publications
4
19
0
Order By: Relevance
“…It should be emphasized that the condensation particle counter quantifies only solid phase (non-volatile particles). The observed decrease in PN emissions agrees with a recent engine dynamometer study (Reference [16]). In that study, the authors concluded that as ethanol content increases, the contribution of the fuel to particulate material falls, while the contribution of the lubricating oil rises.…”
Section: Particle Emissionssupporting
confidence: 91%
“…It should be emphasized that the condensation particle counter quantifies only solid phase (non-volatile particles). The observed decrease in PN emissions agrees with a recent engine dynamometer study (Reference [16]). In that study, the authors concluded that as ethanol content increases, the contribution of the fuel to particulate material falls, while the contribution of the lubricating oil rises.…”
Section: Particle Emissionssupporting
confidence: 91%
“…The molecular weight distribution of the PAH was found to decrease with added ethanol [70,71]. Generally these changes in the particle size distribution can happen when volatile materials are in excess, leaving insufficient solid area available for adsorption and condensation promoting the nucleation process.…”
Section: Noxmentioning
confidence: 99%
“…Studies of particle composition for fuels with high (>50%) alcohol content in gasoline vehicles are scarce. Only Dutcher et al (2011) showed that BC emissions decreased by over 50% with increasing ethanol concentration (E0 to E85) for a portfuel injection flex fuel vehicle (PFI-FFV). This study investigates the particle composition differences in emissions between WG-GDI, SG-GDI, and FFVs with varying gasoline blends of ethanol and isobutanol.…”
Section: Introductionmentioning
confidence: 99%